Multiple Myeloma-Derived Extracellular Vesicles Impair Normal Hematopoiesis by Acting on Hematopoietic Stem and Progenitor Cells - Laurenzana, Ilaria; Trino, Stefania; Lamorte, Daniela; De Stradis, Angelo; Santodirocco, Michele; Sgambato, Alessandro; De Luca, Luciana; Caivano, Antonella (Frontiers in Medicine, 2021)
Multiple Myeloma (MM) is characterized by the abnormal proliferation of clonal plasma cells (PCs) in bone marrow (BM). MM-PCs progressively occupy and likely alter BM niches where reside hematopoietic stem and progenitor cells (HSPCs) whose viability, self-renewal, proliferation, commitment, and differentiation are essential for normal hematopoiesis. Extracellular vesicles (EVs) are particles released by normal and neoplastic cells, including MM cells. They are important cell-to-cell communicators able to modify the phenotype, genotype and fate of the recipient cells. Investigation of mechanisms and mediators underlying HSPC-MM-PC crosstalk is warranted to better understand the MM hematopoietic impairment and for the identification of novel therapeutic strategies against this incurable malignancy. This study aims to evaluate whether EVs released by MM-PCs interact with HSPCs, what effects they exert, and the underlying mechanisms involved. Therefore, we investigated the viability, cell cycle, phenotype, clonogenicity and microRNA profile of HSPCs exposed to MM cell line-released EVs (MM-EVs). Our data showed that: i) MM cells released an heterogeneous population of EVs; ii) MM-EVs caused a dose-dependent reduction of HSPCs viability, iii) MM-EVs caused a redistribution of the HSPC pool characterized by a significant increase in the frequency of stem and early precursors accompanied by a reduction of late precursor cells, including common myeloid progenitors, megakaryocyte erythroid progenitors and B and NK progenitors, and a slight increase of granulocyte macrophage progenitors; iv) MM-EVs caused an increase of stem and early precursors in S phase with a decreased number of cells in G0/G1 phase in a dose-dependent manner; v) MM-EVs reduced the HSPC colony formation; vi) MM-EVs caused an increased expression level of C-X-C motif chemokine receptor type 4 (CXCR4) and an activation of miRNAs. In conclusion, MM cells through the release of EVs, by acting directly on normal HSPCs, negatively dysregulate normal hematopoiesis and this could have important therapeutic implications.